2013
DOI: 10.4314/ahs.v13i3.29
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammatory cells and damaged limbal cells in pterygium

Abstract: Background: Chronic inflammation in pterygium occurrence has not been explained. Whether damaged limbal basal epithelial cells are associated with pterygium occurrence in black Africans is not clear. Objective: To explain chronic inflammation in pterygium, and to clarify whether damaged limbal basal epithelial cells were associated with pterygium occurrence in black Africans. Methods: Chronic inflammatory changes and damaged limbal basal epithelial cells were assessed in 59 samples. Results: Chronic inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Therefore, upregulation of TLR5 in the epithelium of the conjunctival tissues of SJS, OCP, and chemical eye burns might be involved in the chronic inflammation of these respective diseases. Although it has been reported that there are chronic inflammatory cells in pterygium,15 the difference of the extent of TLR5 expression between pterygium and the devastating ocular surface disorders might suggest the different quality of the chronic inflammation.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, upregulation of TLR5 in the epithelium of the conjunctival tissues of SJS, OCP, and chemical eye burns might be involved in the chronic inflammation of these respective diseases. Although it has been reported that there are chronic inflammatory cells in pterygium,15 the difference of the extent of TLR5 expression between pterygium and the devastating ocular surface disorders might suggest the different quality of the chronic inflammation.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that those pterygia had stopped growing thus; young age is not tantamount to progress. Since MMPs are underexpressed in fibroblasts and stroma of individuals with chronic solar conjunctivitis, 16 suggesting presence of transforming growth factor-beta, 17 we imagine that a decrease in available growth factors to a level that is insufficient to promote fibrovascular proliferation that causes pterygium, yet enough to suppress MMPs may well explain lack of pterygium progress. Fibroblast mitotic rate has been shown to be proportional to the level of growth factors.…”
Section: 2mentioning
confidence: 99%
“…Anguria et al (16) also showed chronic inflammatory cell activation and presentation in pterygium pathology specimens. In addition, the cell counts were related to the severity of the inflammation and UV exposure was suspected as being responsible for the induced inflammatory cells in pterygium tissues.…”
Section: Discussionmentioning
confidence: 92%